Analisa Penjadwalan Produksi Emergency Air Reciever dengan Menggunakan Master Production Schedule di PT. Boma Bisma Indra - Assaabiq, Muchammad; Diah Yuniawati, Ratna (Jurnal Jaring SainTek, 2022)
PT Boma Bisma Indra (Persero) is a State-Owned Enterprise (BUMN) which has 3 divisional business units, one of which is the industrial machinery and equipment division (MPI) and the foundry unit located on Jl. Imam Bonjol No. 18 Bugul Lor, Pasuruan City, East Java. The industrial machinery and equipment division and foundry unit (MPI) located in Pasuruan has grown rapidly as a company that focuses on manufacturing machinery and produces products such as Oil & Gas/ Refinery / Petrochemical Industries, Power plans, Iron Casting, and Pressure Vessels. In PT. Boma Bisma Indra, whose orientation is a make-to-order company, where the new company will procure raw materials and run production if there is a request from the customer. Difficulties that are often encountered in make-to-order companies are delays in the arrival of raw materials, and process delays caused by inadequate workers. Therefore, a method called the Master Production Schedule (MPS) is needed where this method will determine the time period that will be required for each process starting from the preparation of documents related to procedures and product specifications to the finishing fabrication process. This research focuses on timeliness analysis in every process in the master production schedule using the master production schedule (MPS) method